2011
DOI: 10.1002/sia.3791
|View full text |Cite
|
Sign up to set email alerts
|

Rapid quantitative analysis of fayalite and silica formed during decarburization of electrical steel

Abstract: Subscales on surfaces are affected by the temperature and oxidation potential during decarburization annealing of electrical steel containing 3 wt% silicon. Knowledge of the structural and chemical properties of the surface oxide layer subscales permits the control of high-temperature oxidation processes in the electrical steel. In the present work, the oxide layers were characterized by transmission electron microscopy (TEM), Fourier transform infrared (FTIR) spectrometry, and glow discharge optical emission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…The glow discharge sampling was successfully employed to carry out the comprehensive analysis of the chemical information and microscopic features of the oxide layers in the direction of depth. Based on the previous analytical results of decarburized steel sheets by GD‐OES for their in‐depth compositional profile and by cross‐sectional SEM to observe the microstructure, the cross‐section‐specific depths were analyzed by XPS, FTIR spectrometry, scanning electron microscope, and transmission electron microscope. In particular, the equilibrium and kinetic considerations served by theoretical calculations of selective oxidation were examined in an attempt to understand the formation and behavior of the oxide layers, and their results were discussed in association with the above analytical results.…”
Section: Introductionmentioning
confidence: 99%
“…The glow discharge sampling was successfully employed to carry out the comprehensive analysis of the chemical information and microscopic features of the oxide layers in the direction of depth. Based on the previous analytical results of decarburized steel sheets by GD‐OES for their in‐depth compositional profile and by cross‐sectional SEM to observe the microstructure, the cross‐section‐specific depths were analyzed by XPS, FTIR spectrometry, scanning electron microscope, and transmission electron microscope. In particular, the equilibrium and kinetic considerations served by theoretical calculations of selective oxidation were examined in an attempt to understand the formation and behavior of the oxide layers, and their results were discussed in association with the above analytical results.…”
Section: Introductionmentioning
confidence: 99%
“…19) Jung et al have indicated that the Fourier transform infrared (FTIR) spectrometry and glow discharge optical emission spectrometry (GD-OES) may be used for the rapid quantitative analysis of fayalite and silica in surface oxide layers. 20) In this paper, the optimum annealing condition of decarburization was studied by carbon-sulfur infrared analyzer under different annealing temperature and P H2O /P H2 . The evolution of oxides morphology in oxidized layer and the concentration distribution trend of silicon and oxygen in oxidized layer were observed by Scanning Electron Microscopy and Glow Discharge Spectrometer at different annealing time.…”
Section: Effect Of Annealing Time On Oxides Phases and Morphology Alomentioning
confidence: 99%
“…When P H2O /P H2 reaches a certain level, water vapor reacts with iron to generate FeO, which further react with SiO 2 to generate Fe 2 SiO 4 particles. [4][5][6] When P H2O /P H2 is sufficiently high, Fe 2 O 3 is generated, which may react with FeO to form Fe 3 O 4 . [7][8][9] Stratton and Stanescu 10) found that the decarburization rate is faster under an atmosphere of N 2 + H 2 + H 2 O than under a carbonaceous-type atmosphere.…”
Section: Introductionmentioning
confidence: 99%